Pengaruh Program Lumajang Taqwa, Lumajang Cerdas, Lumajang Sehat, Lumajang Makmur dan Lumajang Peduli Terhadap Pencapaian Visi Misi Badan Amil Zakat Nasional Kabupaten Lumajang Tahun 2018 - Achmad Farid; Istiana Umil Mahtum (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
Data processing is performed using t-test testing techniques. In processing the data the researchers used the help of IBM SPSS statistical computer assistant application program 20. Based on the results of data analysis, the results showed that